2022
DOI: 10.1186/s13006-022-00478-5
|View full text |Cite
|
Sign up to set email alerts
|

A review of the disruption of breastfeeding supports in response to the COVID-19 pandemic in five Western countries and applications for clinical practice

Abstract: Background The COVID-19 pandemic has significantly altered how breastfeeding support is provided, resulting in mixed breastfeeding outcomes and experiences for mothers. The World Health Organization has consistently supported breastfeeding from the beginning of the pandemic. However, recommendations from obstetrical and gynaecological societies within individual countries have varied in their alignment with this guidance, resulting in inconsistent recommendations. It is unknown how breastfeedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…Some of the papers highlighted the impact of separation between mothers and infants and between mothers and birth companions on breastfeeding rates. 24 , 25 The papers by Gribble et al 26 and Brown and Shenker 8 highlighted the unnecessary and detrimental impact of separating mother-infant dyads after birth, and particularly for those with additional vulnerabilities due to being born premature and/or sick, with Gribble et al 26 arguing how this occurred “despite no evidence of risks”. In the paper by Brown and Shenker, approximately a quarter of mothers who had an infant in the neonatal unit were told that they could not visit their infant, and this lack of contact was significantly associated with breastfeeding cessation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the papers highlighted the impact of separation between mothers and infants and between mothers and birth companions on breastfeeding rates. 24 , 25 The papers by Gribble et al 26 and Brown and Shenker 8 highlighted the unnecessary and detrimental impact of separating mother-infant dyads after birth, and particularly for those with additional vulnerabilities due to being born premature and/or sick, with Gribble et al 26 arguing how this occurred “despite no evidence of risks”. In the paper by Brown and Shenker, approximately a quarter of mothers who had an infant in the neonatal unit were told that they could not visit their infant, and this lack of contact was significantly associated with breastfeeding cessation.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of professional support during the pandemic was highlighted, often associated with limited in-person breastfeeding support in the hospital unit and within the community, 8 , 24 , 25 , 31 with some women reporting that they felt they were doing it “on their own”. 34 While women were generally able to access different types of support, eg, health professionals and lactation consultations, 32 the quality and quantity of support were restricted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first weeks of the emergency, there was no evidence about the possibility of vertical transmission of SARS-CoV-2 through breastfeeding or human milk and the literature on vertical transmission of other coronaviruses (MERS or SARS) was very poor ( 8 10 ). Several studies showed how this uncertainty affected breastfeeding rates ( 11 ). The authors of an Italian study enrolled 204 mothers during the first lockdown and compared them to a group of 306 mothers who took part in a previous study.…”
Section: Introductionmentioning
confidence: 99%